Traditional Cultural Expression as an Embodiment of Indigenous Communities and Regional Identity (Semarang Indonesia Case) - Rindia Fanny Kusmaningtyas; Arif Hidayat; Gabrielle Poetri Soebiakto; Ahmad Fauzan Permana; Ibadurrahman Hanan Abdullah (Universitas Negeri Semarang, 2023)
Traditional Cultural Expressions include forms of Communal Intellectual Property, which can become an identity for an indigenous people. Traditional Cultural Expressions have a potential for Intellectual Property protection which is beneficial for the economy of indigenous peoples. This study aims to find out and analyze the existence of Traditional Cultural Expressions as the embodiment of indigenous peoples and regional identity in the Semarang Residency and the influence of its development on the regional economy in the Semarang Residency. The results of this study indicate that a Traditional Cultural Expression in the Residency of Semarang has shown its existence in terms of its art and traditional culture which has become an identity that differentiates it from arts/culture in other areas, so that it has the potential to improve the economy in the Residency of Semarang. In view of the Regulations to protect Traditional Cultural Expressions it is appropriate to be able to register Traditional Cultural Expressions as Intellectual Property. However, there are still obstacles in implementing the law, such as the lack of activeness of the Government in providing socialization and coordination of data collection and identification to protect Traditional Cultural Expressions with Communal Intellectual Property and the lack of role and knowledge of the community in identifying traditional arts and culture in obtaining protection by way of register Intellectual Property, especially Copyrights that have existed for generations.